Cranioplasty: A Single Institute Retrospective Descriptive Study - Koirala, Sagar; Pandey, Rajshree; Adhikari, Serina; Devkota, Manjari; Bishokarma, Suresh; Shrestha, Pratyush; Thulung, Suraj; Yogi, Nikunja (Nepal Journal of Neuroscience, 2025)
Introduction: Decompressive craniectomies are among the most common procedures in neurosurgery, performed for conditions such as stroke or trauma. Patients who survive the initial insult require cranioplasty to cover the defect initially created to decrease intra cranial pressure. This study explores the common indication, types and potential complications of cranioplasty. Methodology: A retrospective descriptive study was performed at a tertiary neurosurgical referral hospital. It included all patients who underwent cranioplasty over a five-year period. Data was collected on the demographics, type of cranioplasty, indication and complications. It was tabulated and studied using Microsoft excel. Results: Total of 162 patients (67.5%) underwent cranioplasty out of 240 decompressive craniectomies. The patients ranged in age from 12 to 72 years, with twice as many men undergoing cranioplasty compared to women. The most common indication were craniectomies for trauma, followed by ischemic stroke. Acrylic cranioplasty was performed in 110 patients, autologous in 39 and titanium in 4 patients. Infection was the most common complication, occurring in 2.5% of cases, followed by seizure in 1.2%. Conclusion: Cranioplasty is a common and generally safe procedure for patient who have undergone craniectomies for various conditions. The most frequent complications are infections and seizures.